2009
DOI: 10.1126/science.1166527
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphism in npr-1 Is a Behavioral Determinant of Pathogen Susceptibility in C. elegans

Abstract: The nematode Caenorhabditis elegans responds to pathogenic bacteria with conserved innate immune responses and pathogen avoidance behaviors. We investigated natural variation in C. elegans resistance to pathogen infection. With the use of quantitative genetic analysis, we determined that the pathogen susceptibility difference between the laboratory wild-type strain N2 and the wild isolate CB4856 is caused by a polymorphism in the npr-1 gene, which encodes a homolog of the mammalian neuropeptide Y receptor. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
293
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 223 publications
(302 citation statements)
references
References 22 publications
6
293
2
1
Order By: Relevance
“…The previously reported characterization of mucoid P. aeruginosa PA14 mucD included the killing of C. elegans N2 (26). We have shown that a marked difference in susceptibility between C. elegans N2 wild type and strains with diminished NPR-1 activity, such as npr-1(lf) mutants and wild strains such as CB4856, results from the effects of NPR-1 on C. elegans behavioral avoidance (17). Because mucoid strains do not elicit NPR-1-mediated behavior, we anticipated that N2 and CB4856 strains should exhibit the same susceptibility to killing by a lawn of mucoid P. aeruginosa.…”
Section: Elegans Mutants Defective In Oxygen Sensation Have Enhancedmentioning
confidence: 99%
See 3 more Smart Citations
“…The previously reported characterization of mucoid P. aeruginosa PA14 mucD included the killing of C. elegans N2 (26). We have shown that a marked difference in susceptibility between C. elegans N2 wild type and strains with diminished NPR-1 activity, such as npr-1(lf) mutants and wild strains such as CB4856, results from the effects of NPR-1 on C. elegans behavioral avoidance (17). Because mucoid strains do not elicit NPR-1-mediated behavior, we anticipated that N2 and CB4856 strains should exhibit the same susceptibility to killing by a lawn of mucoid P. aeruginosa.…”
Section: Elegans Mutants Defective In Oxygen Sensation Have Enhancedmentioning
confidence: 99%
“…In contrast, npr-1(lf) mutants and strains carrying the 215F allele of npr-1 do not leave the lawn of P. aeruginosa because of an overriding hyperoxia avoidance (Fig. S1) (17). This NPR-1-dependent behavioral difference in the presence of pathogenic bacteria underlies the difference in susceptibility between N2 and npr-1 mutants (17).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This locus is of interest as the lab-derived (McGrath et al, 2009), N2 allele of npr-1 has been found to be important in a number of phenotypes (for example, Doroszuk et al, 2009;McGrath et al, 2009;Reddy et al, 2009;Gaertner et al, 2012). This locus was therefore investigated using the isolate DA650, which contains the g320 npr-1 allele from RC301 backcrossed 10 times into an N2 background (Gloria-Soria and Azevedo, 2008), and isolates DA609 and DA508, which contain different npr-1 loss-offunction alleles (de Bono and Bargmann, 1998).…”
Section: Qtl Confirmationmentioning
confidence: 99%